(untitled) (Swiss Medical Weekly, 2024)
BACKGROUND: Chronic musculoskeletal pain syndromes, including fibromyalgia, are heterogeneous entities with a major socioeconomic burden. Multimodal treatment programmes have shown greater efficacy than conventional approaches for these patients, at least in the short term. A profound understanding of chronic musculoskeletal pain syndrome patients treated in multimodal treatment programmes is important for their development and to provide insight into these conditions. AIM: To provide a comprehensive and objective description of medical, psychosocial and sleep characteristics of the treatment-refractory chronic musculoskeletal pain syndrome patients treated at the multimodal treatment programmes provided by our tertiary service in Switzerland. METHODS: This was a cross-sectional analysis of 202 refractory chronic musculoskeletal pain syndrome patients with or without a concomitant autoimmune disorder hospitalised between 2018 and 2022 in a 12-day Swiss multimodal treatment programme. They underwent a comprehensive self-assessment with eight different questionnaires and assessments by a psychiatrist, rheumatologist, pain specialist, occupational therapist and physiotherapist. Sleep assessment was performed via actigraphy. Clinical and demographic variables were selected by consensus of three experienced rheumatologists and chronic pain specialists. The Fibromyalgia Rapid Screening Test (FiRST), American College of Rheumatology (ACR)-2010 criteria (ACR2010) and Toronto Alexithymia Scale-20 (TAS-20) were also applied. RESULTS: The mean age of the patients was 47 years (SD = 10), 73% were female, and 30% were obese. Half (50%) were not from Switzerland, and 12% came from conflict zones. Almost half (40%) lived alone. Back pain was the principal site (90%). Of the patients, 78% fulfilled the ACR2010 criteria for fibromyalgia, and 17% were diagnosed with an underlying immune-mediated disorder, mostly spondylarthritis. Pain since childhood occurred in 45% of the patients, and 68% had pain since adolescence. Disability financial aid had been pursued by 69%, and 46% were still awaiting a response. Psychiatric comorbidities were highly prevalent (73%), of which 56% consisted of depression. Of all patients, 15% were diagnosed with enduring personality changes after a catastrophic experience (EPCACE), and 10% had post-traumatic stress disorder. Alexithymia affected 34% of patients. Objective sleep disorder was observed in 78% of patients, and 41% were under opioid therapy. CONCLUSION: This analysis reveals the complex psychosomatic and socioeconomic patterns of the patients treated in Switzerland with refractory chronic musculoskeletal pain syndromes, often originating in childhood and adolescence. Obesity, immigration, social isolation, psychiatric comorbidities, sleep deprivation and opiate use, among others, stood out as target characteristics for further research.